General Practice Referrals to a Department of Neurology - Wiles, C M (J R Coll Physicians Lond, 1996)
OBJECTIVE: Assessment of general practitioner (GP) new referrals to a neurology department in terms of satisfaction for patient and doctor. DESIGN: Prospective study by questionnaire of patients, GPs and specialists. SETTING: Neurology hospital outpatient clinics. SUBJECTS: 339 consecutive new outpatients. MAIN OUTCOME MEASURES: Overall patient satisfaction with clinic attendance, with allocated time and waiting times after referral; GPs' reasons for referral, and satisfaction with outcome; specialists' actions in the clinic, views on referral. RESULTS: Some 67% of patients found the referral helpful; 23% felt there was insufficient time to explain fully their problem. Nearly half of the patients had waited ≥6 months for an appointment. The GP was uncertain of the diagnosis at referral in 76% of cases and found information from the clinic useful in 89%. Specialists made a new diagnosis in 40% of referrals, discharged 73% (with or without investigation) and admitted 11%; 76% of referrals were felt to be appropriate. CONCLUSIONS: Patients and GPs usually found the referral helpful. Seeing patients more briefly is inappropriate since almost a third already felt consultation time to be short. Although some referrals may have been inappropriate, the dominant deficiency in the service was the time they had to wait after the referral. To satisfy local need, it is estimated that twice the present number of consultant neurologists would be required.